2019
DOI: 10.1289/ehp3730
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peroxisome Proliferator–Activated Receptor Gamma (PPARγ) in Mono(2-ethylhexyl) Phthalate (MEHP)-Mediated Cytotrophoblast Differentiation

Abstract: Background:Phthalates are environmental contaminants commonly used as plasticizers in polyvinyl chloride (PVC) products. Recently, exposure to phthalates has been associated with preterm birth, low birth weight, and pregnancy loss. There is limited information about the possible mechanisms linking maternal phthalate exposure and placental development, but one such mechanism may be mediated by peroxisome proliferator–activated receptor γ (PPARγ). PPARγ belongs to the nuclear receptor superfamily that regulates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 77 publications
5
35
0
Order By: Relevance
“… 82 Perinatal phthalate exposures lead to perturbation of methyl donor levels and global hypomethylation in rat testis, 83 and administration of the methyl donor choline attenuates the teratogenic effects of phthalate exposure in chick embryos, 84 suggesting that phthalates may interfere with 1-carbon metabolism. Moreover, phthalates have been reported to bind to and modulate the activity of nuclear hormone receptors, including peroxisome proliferator-activated receptors (PPARs), 85 , 86 which function in part through regulation of DNAm. 87 , 88 Studies to determine the sex-specific mechanistic basis for DEHP-induced perturbations in cardiac DNAm are currently underway.…”
Section: Discussionmentioning
confidence: 99%
“… 82 Perinatal phthalate exposures lead to perturbation of methyl donor levels and global hypomethylation in rat testis, 83 and administration of the methyl donor choline attenuates the teratogenic effects of phthalate exposure in chick embryos, 84 suggesting that phthalates may interfere with 1-carbon metabolism. Moreover, phthalates have been reported to bind to and modulate the activity of nuclear hormone receptors, including peroxisome proliferator-activated receptors (PPARs), 85 , 86 which function in part through regulation of DNAm. 87 , 88 Studies to determine the sex-specific mechanistic basis for DEHP-induced perturbations in cardiac DNAm are currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…This study observed that higher levels of MEHP in cord blood were associated with decreased gestational age at delivery. The reason for the conflicting results is that phthalates and their metabolites, such as DEHP and mono-(2-ethylhexyl) phthalate MEHP, can modulate both PPAR [ 157 , 158 ] and prostaglandins [ 153 , 154 ]. PPARs are necessary for maintaining a pregnancy.…”
Section: Phthalates’ Action On Female Reproductive Healthmentioning
confidence: 99%
“…PPARs are necessary for maintaining a pregnancy. DEHP and its metabolites could bind to PPAR and prevent the maternal–fetal communication which allows birth to be initiated [ 157 , 158 ]. Prostaglandins are signaling molecules, which induce contractions of the uterus, leading to birth or abortion.…”
Section: Phthalates’ Action On Female Reproductive Healthmentioning
confidence: 99%
See 2 more Smart Citations